Beyond the Boundaries of Definitions: Building an Effective, New and Multicriteria Impact Investing Assessment Tool - Fernández, José Luis Fernández (Archīum Ateneo, 2021)
Impact investing was established with the objective of facing social problems through investments with a dual return: a financial plus social and/or environmental return. However, academics have not reached a consensus on the definition of impact investing, and there is a gap in the literature regarding the fundamental criteria of impact investing. This lack of consensus has produced serious problems for impact investors, one of which is that investors cannot clearly define their impact expectations at the time of investment, which makes their decision-making processes groundless. For this reason, this study reviews the concept of impact investing and proposes an investment selection model based on several criteria. Through the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), i.e., a method for multicriteria analysis, we propose an investment selection model as a new, more effective impact investing assessment tool. This model is based on a series of aspects, which cover the three main categories that after having carried out an in-depth revision of the relevant literature. This study contributes to filling the gap in the literature about the definition of and criteria for impact investing. In addition, it presents a practical contribution because the impact investing assessment tool will be able to help impact investors make more accurate investment decisions. By using the assessment approach presented in this paper, impact investors will be able to compare, in a systematic way, the different options for investment and to prioritize those that best align with the impact criteria.